INTEGRASI PASAR MINYAK SAWIT INDONESIA DAN DUNIA - Septika Arifianti; Dwidjono Hadi Darwanto; Slamet Hartono (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
This research was aimed: (1) to measure market intionegration of minyak sawit in the various Indonesia, Malaysia dan Rotterdam; (2) to measure the integration between minyak sawit markets and the substitution markets of minyak sawit ( world market of soybean oil, world market of sunflower oil, world market pf rapesseed oil); and (3) to analyze the leading market of minyak sawit. This research was basd on monthly orice data from 1999 t 2008, taken from World Bank. Market integration was analyzed by using Eagle and Granger model of c-integration. Granger causality test was used to measure the leading market. The result showed that Indonesian minyak sawit market is integrated strongly with minyak sawit market in Malaysia and Rotterdam. Malaysian minyak sawit market isintegrated weakly with Rotterdam minyak sawit market. The analysis of co-integration showed that there were integration between minyak sawit market and substitution markets of minyak sawit. Minyak sawit market also is integrated with the petroleum oil market. Granger causality test showed that Malaysian minyak sawit market was leading to other minyak sawit market. The last, this research suggested that increasing quality control, monitoring behavior of minyak sawit price in the Malaysia and Rotterdam market, and supporting government policies might be needed to increase Indonesian minyak sawit price.